The mental health impact of contact with COVID-19 patients on healthcare workers in the United States. (February 2022) - Hurst, Kelly T.; Ballard, Elizabeth D.; Anderson, Grace E.; Greenstein, Dede K.; Cavanaugh, Grace W.; Dwyer, Elspeth; Swartz, Kimberly; Zarate, Carlos A.; Chung, Joyce Y.; Park, Lawrence T.
Highlights: US healthcare workers (HCWs) were surveyed early in the COVID-19 pandemic. HCWs directly caring for COVID-19 patients reported more negative mental health symptoms. HCWs with more frequent patient contact reported more negative mental health symptoms. Additional data are needed from more diverse and representative samples. Abstract: This study assessed the relationship between contact with COVID-19 patients and the mental health of healthcare workers (HCWs) in the United States (US). In a convenience sample of 957 HCWs who completed an anonymous online survey between April-May 2020, HCWs who provided direct care to confirmed or suspected COVID-19 patients reported increased depressive and posttraumatic symptoms compared to HCWs with no COVID-19 patient contact. Additionally, more frequent contact was associated with higher distress. More data drawn from diverse samples that better represent US HCWs are needed to fully assess the scope of this association.